Cognitive-behaviour therapy for depression: Problems and perspectives - Williams, J (1984)
A number of reviews of the effectiveness of cognitive behaviour therapy for depression, though optimistic, have pointed to some difficulties in interpretation of the outcome literature. These difficulties, and the extent to which more recent research has dealt with them, are reviewed. It is suggested that while some of the genuine difficulties have been resolved, and other commonly expressed may prove to be unfounded, there remain a number of important areas of ignorance which demand further investigation.